Religious and Ethnic Revival in a Chinese Minority: The Bai People of Southwest China - Yongjia, Liang (Routledge Religion in Contemporary Asia Series, 2018)
Situating the field -- Removing religions in the 1950s and the early 1960s -- Introducing ethnicity: the promise of the utopian alterity -- Ethnicity perpetuated: Nanzhao history between China and Thailand -- Religious revival in Dali and Xizhou -- Culturalization of religion and ethnicity -- Temple lost, temple regained: the sacred public space.